Rozwiąż nierówność:
b) x\6 - 1 < 1\3 -x\2
d) x-3\2 + 3\2 > x+3\4 + x-1\8
f) x+5\3 - 2 ≤ x-3\4 - x+4\3 + 1\6
h) x\3 + 3 ≥ 1-x\7 + 22\21

b) 0,2(x+2) < 4,4 - x
d) -0,08(10x-5) ≤ 0,1(x-20) + 0,4
f) 5(0,16x-0,01) < 0,2(1-x)
h) 0,35(x+2) - 0,05(x+14) > 0,2(2x + 3) + 1,7

Uwaga: Takie wyrazy jak x-3\2 czy x\6 to są ułamki zwykłe.

1

Odpowiedzi

2009-12-15T14:27:43+01:00
B) x\6 - 1 < 1\3 -x\2

x/6+x/2<1+⅓
x/6+3x/6<4/3
4x/6<4/3
2x/3<4/3 /2/3
x<2

d) x-3\2 + 3\2 > x+3\4 + x-1\8

x-x-x>¾-⅛
-x>6/8-⅛
-x>⅝
x<-⅝

f) x+5\3 - 2 ≤ x-3\4 - x+4\3 + 1\6

x-x+x≤-¾+4/3+1/6-5/3
x≤-9/12+16/12+2/12-20/12
x≤-11/12

h) x\3 + 3 ≥ 1-x\7 + 22\21

x/3+x/7≥22/21-3
7x/21+3x/21≥22/21-63/21
10x/21≥-41/21 ×(21/10)
x≥-41/10
x≥-4 1/10



b) 0,2(x+2) < 4,4 - x

0,2x+0,4<4,4-x
0,2x+x<4,4-0,4
1,2x<4
1 1/5x<4
6/5x<4 ×(5/6)
x<10/3
x<3 ⅓

d) -0,08(10x-5) ≤ 0,1(x-20) + 0,4

-0,8x+0,4≤0,1x-2+0,4
0,1x+0,8x≥2+0,4-0,4
0,9x≥2
9/10x≥2 ×(10/9)
x≥20/9
x≥2 2/9

f) 5(0,16x-0,01) < 0,2(1-x)

0,8x-0,05<0,2-0,2x
0,8x+0,2x<0,2+0,05
x<0,25

h) 0,35(x+2) - 0,05(x+14) > 0,2(2x + 3) + 1,7

0,35x+0,7-0,05x-0,7>0,4x+0,6+1,7
0,4x+0,05x-0,35x<-1,7-0,6
0,1x<-2,3
x<-23
1 5 1